Design and Control of Ultrasound Image-guided Prostatic Brachytherapy Robot - Sun, Yue; Dai, Xuesong; Yin, Qihao; Ju, Linfeng; Tang, Xiaolan; Li, Miao (Recent Patents on Mechanical Engineering, 2024)
Background: With the continuous development of medical robots, they have become a powerful tool for surgery and treatment. A prostate brachytherapy robot is a kind of robot widely used in prostate cancer treatment; its main function is to accurately implant radioactive seeds into prostate tissue to kill cancer cells. Using prostate brachytherapy robots for surgery can reduce damage to surrounding tissue during surgery, thereby reducing the risk of external electrolysis and metastasis of tumor cells. Objective: This study aimed to design a prostate brachytherapy robot that is more in line with practical usage needs, based on the method of manually performing prostate brachytherapy surgery in clinical practice. Finally, its feasibility has been demonstrated through brachytherapy experiments. Methods: Firstly, the actual requirements for prostate particle implantation surgery have been analyzed, which has been followed by reviewing previous literature and patents to determine the design scheme of the robot. Finally, SOLIDWORKS software has been used for mechanical design of the robot, and the control system of the robot has been designed based on Arduino. Results: A robotic arm type prostate particle implantation robot has been successfully designed. We have installed a visual module on the prostate particle implantation robot, which has enabled the robot system to have image transmission monitoring function to assist in the calibration of the puncture position before surgery. Finally, we have employed other sensors to complete the particle implantation experiment, and successfully confirmed its superiority through comparing errors. Conclusion: This work has analyzed and studied the clinical process of prostate particle implantation surgery, and designed a prostate particle implantation robot, including the mechanical design and control system design of the robot. We have also simulated the scene of prostate particle implantation surgery in the human body through particle implantation experiments, and successfully and accurately implanted radioactive particles to the target. The experimental results have proven the feasibility of the robot. We have made improvements in execution efficiency by using a parallelogram-based robotic arm as the representation of the prostate particle implantation robot and equipped it with a visual module. The visual module collects a video stream of the puncture needle's perspective and provides feedback to the control end to assist in the calibration of the puncture position before surgery, greatly reducing the probability of secondary injury to patients.
Keywords: brachytherapy surgery